Minimum and maximum..?

Algebra Level 4

The inequality:

a x 4 2 x 2 + 3 ( x 2 + 1 ) 2 b a\le \frac { { x }^{ 4 }-2{ x }^{ 2 }+3 }{ { ({ x }^{ 2 }+1) }^{ 2 } } \le b

is always true for any real number x . x. If m m represents the maximum possible value of a , a, and n n represents the minimum possible value of b , b, what is the value of m n ? mn?


The answer is 1.00.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let f ( x ) = x 4 2 x 2 + 3 ( x 2 + 1 ) 2 f(x) = \frac {x^4-2x^2+3} {(x^2+1)^2} is at its extrema (maximum and minimum), when f ( x ) = k f(x) = k ; that is k = a k = a or b b .

That is when f ( x ) = x 4 2 x 2 + 3 ( x 2 + 1 ) 2 = k x 4 2 x 2 + 3 = k ( x 2 + 1 ) 2 f(x) = \dfrac {x^4-2x^2+3} {(x^2+1)^2} = k \quad \Rightarrow x^4-2x^2+3 = k(x^2+1)^2

x 4 2 x 2 + 3 = k x 4 + 2 k x 2 + k ( 1 k ) x 4 2 ( 1 + k ) x 2 + 3 k = 0 \Rightarrow x^4-2x^2+3 = kx^4+2kx^2 + k \quad \Rightarrow (1-k)x^4-2(1+k)x^2+3-k = 0

Now when f ( x ) = k f(x) = k , d f ( x ) d x = 0 4 ( 1 k ) x 3 4 ( 1 + k ) x = 0 \dfrac {df(x)}{dx} = 0\quad \Rightarrow 4(1-k)x^3 - 4(1+k)x =0

x [ ( 1 k ) x 2 ( 1 + k ) ] = 0 x = 0 \Rightarrow x\left[ (1-k)x^2 - (1+k)\right] =0 \quad \Rightarrow x = 0\quad or x 2 = 1 + k 1 k \quad x^2 = \dfrac {1+k}{1-k}

Substituting k = x 4 2 x 2 + 3 ( x 2 + 1 ) 2 k = \frac {x^4-2x^2+3} {(x^2+1)^2} , we have:

x 2 = ( x 2 + 1 ) 2 + x 4 2 x 2 + 3 ( x 2 + 1 ) 2 x 4 + 2 x 2 3 = 2 x 4 + 4 4 x 2 2 = x 4 + 2 2 x 2 1 x^2 = \dfrac {(x^2+1)^2 + x^4-2x^2+3} {(x^2+1)^2 - x^4+2x^2-3} = \dfrac {2x^4+4} {4x^2-2} = \dfrac {x^4+2} {2x^2-1}

2 x 4 x 2 = x 4 + 2 x 4 x 2 2 = 0 \Rightarrow 2x^4 - x^2 = x^4+2 \quad \Rightarrow x^4 - x^2 - 2 = 0

( x 2 + 1 ) ( x 2 2 ) = 0 x = ± 2 \Rightarrow (x^2+1)(x^2-2)=0 \quad \Rightarrow x = \pm \sqrt{2}\quad taking only the real roots.

We find that f ( 0 ) = 3 f(0) = 3\quad and f ( ± 2 ) = 4 4 + 3 ( 2 + 1 ) 2 = 1 3 \quad f(\pm \sqrt{2}) = \dfrac {4-4+3}{(2+1)^2} = \dfrac {1}{3}

m = 1 3 \Rightarrow m = \frac {1}{3}\quad and n = 3 m n = 1 \quad n = 3\quad \Rightarrow mn = \boxed {1}

fixed typo in line 6 (it was x^2=0 or x=(1+k)/(1-k))

Aditya Virani Staff - 6 years, 4 months ago
Shubham Garg
May 31, 2015

let f ( x ) = x 4 2 x 2 + 3 ( x 2 + 1 ) 2 f(x)=\frac{x^4-2x^2+3}{(x^2+1)^2}

manipulating f ( x ) = 1 4 x 2 + 1 + 6 ( x 2 + 1 ) 2 f(x)=1-\frac{4}{x^2+1}+\frac{6}{(x^2+1)^2}

let g ( x ) = + 6 ( x 2 + 1 ) 2 4 x 2 + 1 g(x)=+\frac{6}{(x^2+1)^2}-\frac{4}{x^2+1} is maximum obviously at x = 0 x=0 which is equal to 2

At x = 0 x=0 , f ( x ) = m = 3 f(x)=m=3 which is its maximum value

Now d g ( x ) d x = 0 12 ( x 2 + 1 ) 3 + 4 ( x 2 + 1 ) 2 = 0 \frac{dg(x)}{dx}=0\quad\Rightarrow-\frac{12}{(x^2+1)^3}+\frac{4}{(x^2+1)^2}=0

3 = x 2 + 1 x 2 = 2 \Rightarrow3=x^2+1\quad\Rightarrow x^2=2

Putting x 2 = 2 x^2=2 g ( x ) = 2 3 g(x)=\frac{-2}{3} and f ( x ) = n = 1 3 f(x)=n=\frac{1}{3} which is its minimum value.

Therefore m n = 1 mn=1 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...